Perception of the Online Learning Process During the Covid-19 Pandemic at New Higher Education Institution in Aceh - Nabila Hilmy Zhafira; Amsal Irmalis (Universitas Teuku Umar, 2021)
The expansion of access to education in Indonesia through new higher education institution or PTN-B gives new hope for the future of education. However, the limited condition of human resources, facilities, and infrastructure management processes of each PTN-B greatly impacts the learning process. The diversity of learning methods is present as an alternative solution to these problems, but is not sufficient to accommodate all learning needs. There are three PTN-B in Aceh, Universitas Teuku Umar, ISBI Aceh, and Universitas Samudra. The three PTN-Bs have carried out a learning process outside the network during the Covid-19 pandemic, but this is a relatively new phenomenon in the era of the COVID-19 pandemic. This is a challenge for PTN-B in Aceh, especially to face the COVID-19 era and anticipate global challenges in the future. This study aims to analyze students' perceptions of the application of online learning at PTN-B in Aceh during the Covid-19 pandemic, as well as to find out the assessment procedures for distance learning that have proven to be effectively applied to students according to the conditions/characteristics of students and the characteristics of learning materials. Then this study will evaluate the online learning process through student perceptions and make recommendations for its implementation. This study uses a literature review approach by emphasizing the analysis on numerical data that is processed by literature review methods.